ChemInform Abstract: Synthesis of Oxazolidinylphosphine Chalcogenides (II) from Aminoethyl Vinyl Ethers (I). Issue 16 (22nd April 2014) - Volkov, P. A.; Ivanova, N. I.; Gusarova, N. K.; Oparina, L. A.; Larina, L. I.; Vysotskaya, O. V.; Kolyvanov, N. A.; Bagryanskaya, I. Yu.; Trofimov, B. A.
Abstract via a thermal cyclocondensation reaction